Investigation of La3+ Doped Yb2Sn2O7 as new thermal barrier materials - Wang, Jing; Xu, Fang; Wheatley, Richard J.; Choy, Kwang-Leong; Neate, Nigel C.; Hou, Xianghui (Elsevier, 2015)
Low thermal conductivity is one of the key requirements for thermal barrier coating materials. From the consideration of crystal structure and ion radius, La3+ Doped Yb2Sn2O7 ceramics with pyrochlore crystal structures were synthesised by sol-gel method as candidates of thermal barrier materials in aero-engines. As La3+ and Yb3+ ions have the largest radius difference in lanthanoids group, La3+ ions were expected to produce significant disorders by replacing Yb3+ ions in cation layers of Yb2Sn2O7. Both experimental and computational phase analysis were carried out, and good agreement had been obtained. The lattice constants of solid solution (LaxYb1-x)2Sn2O7 (x=0.3, 0.5, 0.7) increased linearly when the content of La3+ was increased. The thermal properties (thermal conductivity and coefficients of thermal expansion) of the synthesized materials had been compared with traditional 8 wt.% Yttria Stabilized Zirconia (8YSZ) and La2Zr2O7 (LZ). It was found that La3+ Doped Yb2Sn2O7 exhibited lower thermal conductivities than un-doped stannates. Amongst all compositions studied, (La0.5Yb0.5)2Sn2O7 exhibited the lowest thermal conductivity (0.851 W·m-1·K-1 at room temperature), which was much lower than that of 8YSZ (1.353 W·m-1·K-1), and possessed a high coefficient of thermal expansion (CTE), 13.530×10-6 K-1 at 950oC.